The effect of war on prices - Cairnes, John E. (Dublin Statistical Society, 1856)
It is scarcely necessary to say that the common opinion upon this question?an opinion, too, that is shared by some economists of eminence ? is that a state of war necessarily tends to produce a general rise in the prices of commodities. The expression "war-prices" shows what is the popular notion: the doctrine which this expression implies has been supported by some grave and plausible arguments; and it cannot be denied that it is at the present moment countenanced by some very obvious and striking tacts. It will, therefore, not be out of place if I invite the attention of the society for a short space to some of the economic principles which affect this question.
Read January 10th, 1856
Keywords: War; Prices; Commodities; 314.15